2019
DOI: 10.1016/s2352-4642(19)30005-7
|View full text |Cite
|
Sign up to set email alerts
|

MC1R variants in childhood and adolescent melanoma: a retrospective pooled analysis of a multicentre cohort

Abstract: Background: Germline variants in MC1R may increase risk of childhood/adolescent melanoma, but a clear conclusion is challenging because of the limited number of studies and cases. We evaluated the association of MC1R variants and childhood/adolescent melanoma in a large study comparing the prevalence of MC1R variants of childhood/adolescent melanoma patients to that among adult melanoma cases and unaffected controls. Methods: Phenotypic and genetic data on 233 childhood/adolescent (≤20 years) and 932 adult mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Several factors, such as dose of sun exposure, age, gender, fair skin phenotype, and previous keratinocyte skin cancers, are considered as causal factors of initiation and progression of melanoma, with UV-induced damage of DNA as the primary cause of melanoma development [149,150,151]. However, the incidence of melanoma in childhood and at sites that are minimally exposed to the sun are also registered [152,153]. There is hope that genome-wide studies will help to identify the heritable and environmentally-triggered contributors to melanoma risk [153,154,155,156,157].…”
Section: Fgf and Fgfr As Molecular Prognostic Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors, such as dose of sun exposure, age, gender, fair skin phenotype, and previous keratinocyte skin cancers, are considered as causal factors of initiation and progression of melanoma, with UV-induced damage of DNA as the primary cause of melanoma development [149,150,151]. However, the incidence of melanoma in childhood and at sites that are minimally exposed to the sun are also registered [152,153]. There is hope that genome-wide studies will help to identify the heritable and environmentally-triggered contributors to melanoma risk [153,154,155,156,157].…”
Section: Fgf and Fgfr As Molecular Prognostic Markersmentioning
confidence: 99%
“…However, the incidence of melanoma in childhood and at sites that are minimally exposed to the sun are also registered [152,153]. There is hope that genome-wide studies will help to identify the heritable and environmentally-triggered contributors to melanoma risk [153,154,155,156,157]. Another important issue is to correctly prognose the melanoma progression.…”
Section: Fgf and Fgfr As Molecular Prognostic Markersmentioning
confidence: 99%
“…In this study, we found that MC1R variants were almost equally distributed across both groups of patients, those with SPMs and those with MPMs. The correlation between MC1R variants and melanoma risk has been widely described in different populations (Tagliabue et al, 2015 ; Pinto et al, 2016 ; Pellegrini et al, 2019 ). The MC1R gene is considered a master regulator of pigment production and distribution throughout the skin (pigmentary function) (Puig et al, 2005 ) as well as a regulator of antioxidant defenses and DNA repair mechanisms (non-pigmentary function) (Rees, 2004 ; Abdel-Malek et al, 2014 ), thereby supporting its role in melanoma development.…”
Section: Discussionmentioning
confidence: 99%
“…Significant variation exists amongst MC1R and the resultant phenotypes. In the paediatric population, those with cutaneous melanoma have higher rates of MC1R variants than adult populations with cutaneous melanoma, with V60L and D294H having the most influential association 53 . Wendt et al documented that in Austria, MC1R variants are an independent risk factor for melanoma in females but not males 54 .…”
Section: Mutations In the Ultraviolet Controlled Pathwaymentioning
confidence: 99%